Предмет: Алгебра,
автор: HoranDNiall
#1 упростите выражение. #2 решите неравенство
Приложения:
Ответы
Автор ответа:
0
1
(x-y)(x²+xy+y²)/(x+y)(x²-xy+y²)* (x²-xy+y²)/(x-y)=(x²+xy+y²)/(x+y)
2
a)9-(5x-2)/2>x+5
9*2-(5x-2)>2)x+5)
18-5x+2>2x+10
-5x-2x>10-20
-7x>-10
x<10/7
b)7/4+2x/3≤x+5/3
7*3+2x*4≤12*x+5*4
21+8x≤12x+20
8x-12x≤20-21
-4x≤-1
x≥1/4
(x-y)(x²+xy+y²)/(x+y)(x²-xy+y²)* (x²-xy+y²)/(x-y)=(x²+xy+y²)/(x+y)
2
a)9-(5x-2)/2>x+5
9*2-(5x-2)>2)x+5)
18-5x+2>2x+10
-5x-2x>10-20
-7x>-10
x<10/7
b)7/4+2x/3≤x+5/3
7*3+2x*4≤12*x+5*4
21+8x≤12x+20
8x-12x≤20-21
-4x≤-1
x≥1/4
Похожие вопросы
Предмет: Русский язык,
автор: sagyndykovakarly
Предмет: Русский язык,
автор: Apazhev
Предмет: Русский язык,
автор: golem85
Предмет: Математика,
автор: жарик1
Предмет: Биология,
автор: Konfeta0108